A Common fixed point iterative process with errors for quasi-nonexpansive mappings in banach spaces - Pattraporn Kaonein (Prince of Songkla University Faculty of Science (Mathematics and Statistics), 2013)
Thesis (M.Sc., Mathematics and Statistics)--Prince of Songkla University, 2010